2013
DOI: 10.1111/jvh.12114
|View full text |Cite
|
Sign up to set email alerts
|

Modified spleen stiffness measurement by transient elastography is associated with presence of large oesophageal varices in patients with compensated hepatitis C virus cirrhosis

Abstract: Modified spleen stiffness measurement by transient elastography is associated with presence of large oesophageal varices in patients with compensated hepatitis C virus cirrhosis 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 30 publications
(58 reference statements)
6
96
1
Order By: Relevance
“…Nevertheless, noninvasive methods of predicting PH, such as spleen size and platelet count, as well as the ratio between platelet count and spleen size, lack both sensitivity and specificity [15][16][17][18] . Recent studies have demonstrated that PH results not only in an increase in spleen size, but also in modifications of splenic blood flow, tissue hyperplasia, and fibrosis [14,15,19] . Accordingly, spleen stiffness measurement (SSM) may be a valuable tool for assessing the degree of PH, the presence and severity of EVs and the risk of bleeding among patients with chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, noninvasive methods of predicting PH, such as spleen size and platelet count, as well as the ratio between platelet count and spleen size, lack both sensitivity and specificity [15][16][17][18] . Recent studies have demonstrated that PH results not only in an increase in spleen size, but also in modifications of splenic blood flow, tissue hyperplasia, and fibrosis [14,15,19] . Accordingly, spleen stiffness measurement (SSM) may be a valuable tool for assessing the degree of PH, the presence and severity of EVs and the risk of bleeding among patients with chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, spleen stiffness measurement (SSM) may be a valuable tool for assessing the degree of PH, the presence and severity of EVs and the risk of bleeding among patients with chronic liver disease. Recent studies have shown that SSM can assess the severity of PH, the risk of variceal bleeding and the presence of (large) EVs and variceal hemorrhage among patients with cirrhosis, although it cannot predict the grade of EVs [12,14,15,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with Saad et al (16) . Also, SSM and LSM were evaluated by Calvaruso et al (17) , and like our results both of them were sensitive to detect the presence of EV. We observed a highly significant difference in mean SSM values between patients with EV and those without (65.3±26.3versus24.6 ± 13.7 kPa respectively; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the NPV to exclude large varices increased to 100%. This encouraging result would require further confirmation (24). LSM assessed by other methods, such as Acoustic Radiation Force Impulse, shear-wave elastography, and magnetic resonance elastography, has shown promising results but available data is still scarce (25,26).…”
Section: Non-invasive Methods For the Detection Of Vntmentioning
confidence: 97%